MORPHOLOGICAL AND PHYSIOLOGICAL CHANGES OF GROUNDNUT PLANTS BY FOLIAR APPLICATION WITH SALICYLIC ACID - P. JAYALAKSHMI; DEVI, P. SUVARNALATHA; N. D. PRASANNA; G. REVATHI; S. K. SHAHEEN (The Bioscan, 2010)
To study the response of groundnut plant to foliar application of Salicylic acid (100,200 and 400 mg/L) as well as their interaction on vegetative growth, photosynthetic pigments content, yield and some biochemical constituents of groundnut grains. The data indicated that, an enhancement effect of growth characters of plants and yield. The total carbohydrate, fats and proteins in groundnut grains was also increased by 100 or 200 mg/ L of Salicylic acid (SA) application. SA at 400 mg/L recorded the lowest values of yield and above components compared to their corresponding controls.